Ibertia social economy: "Santas Casas da Misericordia" Particular institutions of social solidarity (IPSS) Case study - Juan Antonio Briones Peñalver (AECOOP Escuela de Estudios Cooperativos, 2012)
Organizations operating within Social Economy environment, are contributing to accelerate collective and economic development which give them high levels of Institutional recognition. This recognition acknowledges the important role these institutions are playing in understanding social needs, solving social problems and ensuring increased levels of social equity and employability. Government organizations were not able to provide the activities/solutions offered by social economy organizations. These type of organizations roles and responsibilities are including private, public and commercial activities. Thus, it’s necessary to define discussion and communication channels about what are the entities that enhance collective development between Portugal and Spain. On this paper we have first presented the conceptual framework regarding Iberia social economy (especially Spain and Portugal) and then focus on Portuguese social economy knowledge: we will base our analysis on “Santas Casas da Misericordia”, a particular institution of social solidarity with strong heritage within the Portuguese society.